Evaluation of Platelet-Rich Plasma (PRP) Versus Topical Minoxidil (5%) in Combination with Oral Finasteride for the Treatment of Androgenic Alopecia: Platelet-Rich Plasma Versus Topical Minoxidil and Finasteride - Erfan, Muhammad; Saleem, Sumyra; Hussain, Ashraf; Rana, Mahwash; Ahmed, Sameer; Ali, Amanat (Pakistan Journal of Health Sciences, 2024)
Androgenic alopecia was an inherited condition leading to gradual thinning and loss of hair on the crown and frontal scalp. Objective: To compare efficacy of PRP and topical minoxidil (5%) when used in addition to oral finasteride for treating androgenic alopecia. Methods: This quasi experimental study was conducted at Dermatology Department of Akhtar Saeed Medical and Dental College Rawalpindi from March 2023 to August 2023. Total 80 patients of both genders (40 in each group) aged 18 to 65 years diagnosed with androgenic alopecia. Participants were divided into two treatment groups: Group A received monthly PRP injections oral finasteride and 1 mg daily, while Group B applied topical minoxidil (5%) twice daily oral finasteride 1 mg daily. Efficacy was labeled as a statistically significant increase in mean hair density of at least 20 hair/cm² from pre-treatment to post-treatment using a trichometer. All participants had baseline demographic factors and clinical data. Data were analyzed using IBM SPSS 27.0. Results: The comparison of mean hair density between Group A (PRP and Finasteride) and Group B (Minoxidil and Finasteride) showed that Group A had a significantly higher mean hair density compared to Group B (101.6 ± 11.2 hair/cm² versus 87.0 ± 9.0 hair/cm², p < 0.001), indicating that the treatment in Group A was more effective. Conclusions: This study found that platelet-rich plasma (PRP) as an addition to oral finasteride improves hair regrowth, density, and patient satisfaction more than PRP combined with topical minoxidil.